2019
DOI: 10.1002/app.48760
|View full text |Cite
|
Sign up to set email alerts
|

Controlled aggregation of amphiphilic aggregation‐induced emission polycation and superparamagnetic iron oxide nanoparticles as fluorescence/magnetic resonance imaging probes

Abstract: Fluorescence/magnetic resonance (MR) dual‐mode imaging, which combines the excellent single‐cell sensitivity of fluorescence imaging and the high spatial resolution of MR imaging, has been applied to different biomedical applications. However, the aggregation‐caused quenching characteristic of most fluorescence molecules often put limits in their applications. Herein, a fluorescence/MR dual‐mode imaging probe [polyethylene glycol‐polyethylenimine‐tetraphenylethene (PEG‐PEI‐TPE)/superparamagnetic iron oxide (SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…The sensitivity of the polymer is comparable with previous reports; however, its detection range is higher than most of the reported ranges [ 37 , 41 , 42 ]. For example, Chen et al reported that the synthesis of polyphosphazene microspheres has selectivity for Fe 3+ aqueous solutions and a detection limit of 76 × 10 −9 M (0.076 μM) in a range from 0 to 10 μM [ 37 ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The sensitivity of the polymer is comparable with previous reports; however, its detection range is higher than most of the reported ranges [ 37 , 41 , 42 ]. For example, Chen et al reported that the synthesis of polyphosphazene microspheres has selectivity for Fe 3+ aqueous solutions and a detection limit of 76 × 10 −9 M (0.076 μM) in a range from 0 to 10 μM [ 37 ].…”
Section: Resultssupporting
confidence: 87%
“…For example, Chen et al reported that the synthesis of polyphosphazene microspheres has selectivity for Fe 3+ aqueous solutions and a detection limit of 76 × 10 −9 M (0.076 μM) in a range from 0 to 10 μM [37]. Additionally, Yang et al reports sensitivity for Fe 3+ in N, N dimethylformamide The sensitivity of the polymer is comparable with previous reports; however, its detection range is higher than most of the reported ranges [37,41,42]. For example, Chen et al reported that the synthesis of polyphosphazene microspheres has selectivity for Fe 3+…”
Section: Photoluminescence Properties Of Poly(ani-amps)mentioning
confidence: 61%
“…Water soluble MNP with pAA were synthesized by coprecipitation. [ 50 ] The size was 7.88 ± 2.49 nm according to TEM. Hydrophobic MNP decorated with oleic acid with a diameter of 5.03 ± 0.98 nm were obtained following a thermal decomposition procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting polymers were dialyzed for 3-6 days using dialysis tubes with a mass cut-off of 1000 g•mol -1 . MNP were obtained by following a coprecipitation method 28 and subsequent addition of pAA-AAP.…”
Section: Synthesismentioning
confidence: 99%